Pengaruh Karakteristik Individu terhadap Motivasi Pegawai pada Dinas Kesehatan Provinsi Jambi - Kafita Putri (Universitas Batanghari Jambi, 2019)
The research aims to find out how the characteristics of individual to motivation in Jambi provincial health office. Next also to analyze how the influence of individual characteristics on motivation at the Jambi provincial health office. This study uses a quantitative descriptive method with a form of correlational research that explains the relationship of independent variables with dependent variables. The analysis tool in this study uses simple regression with proof of the hypothesis by statistical tests t. The results showed that individual characteristics had a significant effect on employee motivation at the Jambi provincial health office where it was indicated by t count> t table and prog. sig <a (0.05) while the correlation value of 38.8% meant that there was a very close relationship between variables individual characteristics with employee motivation variables.